Mechanical load in soccer specific sprints - Potthast, W.; Brüggemann, G. P.; Kersting, U. (Book of abstracts of the 6th annual congress of the European College of Sport Science, 15th congress of the German Society of Sport Science. Cologne, 24-28 July 2001, 2001)
Vergl. MF 175355.